(untitled) (Research, Society and Development, 2022)
Objective: To investigate the relationship of stress and musculoskeletal pain, as well as the prevalence, in teleworkers during the Covid-19 pandemic. Methodology: This study is an integrative review. The research was carried out between December 2021 and February 2022, where Pubmed, Lilacs, Scielo and Cochrane databases were used, using keywords such as musculoskeletal pain, pandemic, home office, stress and muscle tension and their respective English terms musculoskeletal, pandemic, home office, stress and muscle tension. Only cross-sectional studies were selected. Result: After the initial search in the databases, 15 articles were found for this study in total, where only 5 articles were included for this research sample. Conclusion: Although the home office is a modality adopted by companies and workers during the pandemic, studies are necessary to develop measures in order to optimize and adapt the home as a healthy work environment for these workers.